Media and mobile devices. In search of El Dorado. - Masip, Pere (Anuario ThinkEPI, 2012)
The spread of mobile devices -smartphones and tablets- does not go unnoticed by media companies, and particularly by press companies, which have seen in mobile content a new and profitable source of income. The aim of this article is to explain how newspapers are adopting mobile strategies and the business model behind their strategies.
Keywords: Mobile devices; Smartphones; Tablets; Mass media; Business models.